2020
DOI: 10.3389/fphar.2020.00141
|View full text |Cite
|
Sign up to set email alerts
|

Local Irradiation Modulates the Pharmacokinetics of Metabolites in 5-Fluorouracil—Radiotherapy–Pharmacokinetics Phenomenon

Abstract: Background: The effects of radiotherapy (RT) on the pharmacokinetics (PK) of 5-FU and 5-fluoro-5,6-dihydro-uracil (5-FDHU) were investigated by animal experiments. Methods: Whole-pelvis RT with 0.5 and 2 Gy was delivered to Sprague-Dawley rats. 5-FU at 100 mg/kg was intravenously infused 24 h after radiation. The pharmacokinetics of 5-FU and 5-FDHU in the plasma and bile system were calculated. Results: The areas under the concentration versus time curve (AUC) of 5-FU in the plasma were reduced by local irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The Hsieh study found that radiation significantly reduced the exposure of 5-fluorouracil and its metabolites in vivo and altered their pharmacokinetic profiles. Compared to radiotherapy or chemotherapy alone, 5-fluorouracil combined with radiotherapy leads to serious hematological and gastrointestinal reactions ( Chen et al, 2017 ; Liu et al, 2020 ). The incidence of adverse reactions of sorafenib in combination with radiotherapy exceeds 30%, and there is evidence that the occurrence of toxic and side effects is closely related to the changes in the pharmacokinetics of sorafenib ( Hsieh et al, 2020 ; Tsai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hsieh study found that radiation significantly reduced the exposure of 5-fluorouracil and its metabolites in vivo and altered their pharmacokinetic profiles. Compared to radiotherapy or chemotherapy alone, 5-fluorouracil combined with radiotherapy leads to serious hematological and gastrointestinal reactions ( Chen et al, 2017 ; Liu et al, 2020 ). The incidence of adverse reactions of sorafenib in combination with radiotherapy exceeds 30%, and there is evidence that the occurrence of toxic and side effects is closely related to the changes in the pharmacokinetics of sorafenib ( Hsieh et al, 2020 ; Tsai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy changes the physiological state of the body and can even cause pathological changes, which affect the absorption, distribution, metabolism, and excretion of chemotherapeutic drugs in the body. This results in a change in the pharmacokinetic profile of drugs known as the “radiotherapy-pharmacokinetic” (“RT-PK”) phenomenon ( Chen et al, 2017 ; Ishiyama et al, 2019 ; Hsieh et al, 2020 ; Liu et al, 2020 ). Studies have also shown that many drugs can be affected by the RT-PK phenomenon and that radiotherapy significantly changes the pharmacokinetics of many chemotherapeutic drugs, such as 5-fluorouracil, cisplatin, sorafenib, and irinotecan.…”
Section: Introductionmentioning
confidence: 99%
“…Both off-target and treatment doses have similar interactions with chemotherapy drugs, such as 5-FU [ 47 , 48 ] and cisplatin [ 49 , 50 ], and multikinase inhibitors, such as sorafenib [ 8 ]. Similarly, the current study also confirmed that off-target and SBRT doses were comparable in their ability to modulate the PK of lenvatinib.…”
Section: Discussionmentioning
confidence: 99%
“…3 When incorporated into DNA, 5FU is bound to the sugar backbone to form 5FUrd, 4 enhancing damage in radiation therapy. 5 It is also noteworthy that 18 F-5-fluorouridine is already known as a probe for measuring tissue proliferation and characterization of tumors in the PET (positron emission tomography) imaging technique. 6…”
Section: Introductionmentioning
confidence: 99%